Influence of vocal and aerodynamics aspects on the voice-related quality of life of older adults - Siqueira, Larissa Thaís Donalonso; Silverio, Kelly Cristina Alves; Berretin-Felix, Giédre; Genaro, Kária Flores; Fukushiro, Ana Paula; Brasolotto, Alcione Ghedini (Journal of Applied Oral Science, 2021)
The pursuit for quality of life urged a better understanding of aspects involved in ageing to minimize its consequences. Although many studies investigated older adults’ voice, aspects affecting this population voice-related quality of life have not yet been explored. Objective: To investigate how aerodynamics and vocal aspects are associated with voice-related quality of life in older adults. Methodology: fifty-six older adults aged 60 years or above – 39 women and 17 men – were evaluated. The following procedures were performed: application of the Voice-Related Quality of Life (V-RQOL) protocol; vocal assessment, including auditory-perceptual and acoustic analysis, from which we obtained fundamental frequency (F 0 ), standard deviation of fundamental frequency (SDF 0 ), shimmer, amplitude perturbation quotient (APQ), jitter, pitch period perturbation quotient (PPQ), and harmonics to noise ratio (HNR); aerodynamic assessment using a spirometer; and maximum phonation time (MPT) for /a/, /s/, /z/ and number counting. Results: older adults tend to present high V-RQOL scores. Among women, roughness, APQ, and HNR parameters were negatively correlated with V-RQOL, whereas F 0 was positively. We found no correlation between spirometry measurements and V-RQOL. MPT for /a/, /z/, and number counting was positively correlated with V-RQOL solely among men. Conclusion: Vocal roughness and acoustic parameters have a negative impact on the quality of life of older women. Respiratory aspects related to the available air support for speaking affected the most the voice-related quality of life of older men.